INDIA, THE LAND OF RETAILING - B. Sheerisha, N.Venkat Rao J.Mounika Reddy,G. Vinesh Kumar (International Journal of Scientific Research and Management (IJSRM), 2013)
Retailing is not only an important aspect of the economic structure but very much a part of our lives. As it contributes 10% of the country’s GDP, it proved that its contribution to the GDP is very much significant. For centuries now, India has been operating within her own unique concept of retailing. David Gilbert has defined retail as “any business that directs its marketing effort towards satisfying the final consumer based upon the organization of selling goods and services as a means of distribution”. It is sure and certain that India will be the destination for retailing as existing Indian middle class purchasing power is increasing at a rapid pace. Rural India can be considered as heart land of retailing. But according to Indian Market Research Bureau (IMRB) study 0.6 million villages in India did not have a retail outlet of any kind, further the outlet density in rural India is lower than that of urban India. It indicates a lot of potential being left untapped. The retail companies are found to be rising in India at a remarkable speed year by year. They brought a revolutionary change in the shopping attitude of the Indian customer. Many global retail giants like TESCO, METRO AG, WAL-MART have already identified the scope of growth in Indian retail industry. As India is the second fastest growing economy of the world, the scope of the Indian retail market is very vast. Investors have excellent investment opportunities in Indian retail sector and allied sectors. India offers highest shop density in the whole world, having almost 1,20,000 shops across the length and breadth of the country India has been ranked high amongst the top 10 FDI destinations of the world.